Analysis Of The Efficiency Of Using A 3-Phase Induction Motor As Pump Drive At PDAM Surya Sembada Surabaya - Dhamar Bagaskara; Praise Slamet (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
An induction motor is an electrical device that converts electrical energy into energy. Electric machines use various types of drives, such as water pumps. Applications in transportation equipment, household equipment transportation tools, and large-scale industry. for several reasons. To get the best performance, the induction motor supply must be checked for quality problems, such as changes to the motor power supply. This research analyzes and measures the effect of three-phase induction motors using different power sources from 380 Volts. The motor used is a 3 phase motor at PDAM Suraya Sembada which is located on Jl. Ngagel Tirto V No. 53, Ngagelrejo, district. Wonokromo, Surabaya, East Java. In completing this research, we used the method of mathematical calculating formulas for validation and comparison. The data taken were current, rpm (speed), voltage, cosphi. This research found that a threephase induction motor at 379 Volts had an effect of 84.27%, while the overall average in this study had an average efficiency value of 73%-75